ANALISIS PENERAPAN COLLABORATIVE LEARNING DALAM PEMBELAJARAN BAHASA ARAB DI SMA MUHAMMADIYAH BOARDING SCHOOL 3 TULANGAN - Ibnu Iqbal, Waritsuddin; By Arifin, Moch. Bahak Udin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of the Collaborative Learning method in Arabic language instruction at SMA Muhammadiyah Boarding School 3 Tulangan and to identify the supporting and inhibiting factors influencing its application. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings reveal that the implementation of Collaborative Learning has been carried out in a limited yet purposeful manner, involving activities such as group discussions, dialogue construction, storytelling, and educational games. This method has proven effective in encouraging active student participation and enhancing both Arabic language skills and interpersonal collaboration. However, several obstacles were encountered during its implementation, including unequal participation among students, limited instructional time, the use of textbooks that do not align with students’ proficiency levels, and weak self-regulation abilities. On the other hand, institutional support, students' enthusiasm, and the application of process-based assessment serve as key success factors. The study recommends strengthening classroom management strategies, adjusting instructional materials, allocating more appropriate learning time, and providing continuous teacher training to optimize the effectiveness of Collaborative Learning in the context of Arabic instruction in a boarding school setting